Assessing photoreceptor structure in patients with traumatic head injury. Issue 1 (24th November 2018) - Braza, Matthew E; Young, Jonathon; Hammeke, Thomas A; Robison, Scott E; Han, Dennis P; Warren, Clinton C; Carroll, Joseph; Stepien, Kimberly E
Abstract : Objective: Previous work using adaptive optics scanning light ophthalmoscopy (AOSLO) imaging has shown photoreceptor disruption to be a common finding in head and ocular trauma patients. Here an expanded trauma population was examined using a novel imaging technique, split-detector AOSLO, to assess remnant cone structure in areas with significant disruption on confocal AOSLO imaging and to follow photoreceptor changes longitudinally. Methods and Analysis: Eight eyes from seven subjects with head and/or ocular trauma underwent imaging with spectral domain optical coherence tomography, confocal AOSLO and split-detector AOSLO to assess foveal and parafoveal photoreceptor structure. Results: Confocal AOSLO imaging revealed hyporeflective foveal regions in two of eight eyes. Split-detector imaging within the hyporeflective confocal areas showed both remnant and absent inner-segment structure. Both of these eyes were imaged longitudinally and showed variation of the photoreceptor mosaic over time. Four other eyes demonstrated subclinical regions of abnormal waveguiding photoreceptors on multimodal AOSLO imagery but were otherwise normal. Two eyes demonstrated normal foveal cone packing without disruption. Conclusion: Multimodal imaging can detect subtle photoreceptor abnormalities not necessarily detected by conventional clinical imaging. The addition of split-detector AOSLO revealed the variable condition of inner segments within confocal photoreceptor disruption, confirming the usefulness of dual-modality AOSLO imaging in assessing photoreceptor structure and integrity. Longitudinal imaging demonstrated the dynamic nature of the photoreceptor mosaic after trauma. Multimodal imaging with dual-modality AOSLO improves understanding of visual symptoms and photoreceptor structure changes in patients with head and ocular trauma.